CERTAIN EXPANSIONS INVOLVING GENERALIZED BASIC HYPERGEOMETRIC FUNCTIONS - Purohit, S. D.; Kalla, S. L. (Matematichki Bilten, 2007)
Some fundamental operators of fractional \(q\)-calculus are used to prove a theorem on an expansion formula for the generalized basic hypergeometric functions. Certain interesting consequences of the theorem are also discussed. This general theorem is then applied to derive a number of expansion formulae for the familiar \(q\)-analogue of various basic hypergeometric functions.